DEVELOPMENT PROCESS OF THE LINGUISTICS AS A SCIENCE IN UZBEKISTAN - Sadullaeva Alfiya Nizamaddinovna (Research Focus International Scientific Journal, 2025)
This article talks about the role of women scientists in the development of science and innovative development in the new Uzbekistan. Thanks to the President, large-scale work is underway in our country to increase the socio-political activity of women, ensure their rights and interests, create decent working and living conditions, realize their intellectual potential, expand their participation in the public life of society and state-building, and support leadership, organization, and entrepreneurial ability. Due to this, attention is paid to ensuring gender equality in various spheres of our society.